Regulatory Dendritic Cells Induced by Bendamustine Are Associated With Enhanced Flt3 Expression and Alloreactive T-Cell Death - Molina, Megan S.; Hoffman, Emely A.; Stokes, Jessica; Kummet, Nicole; Smith, Kyle A.; Baker, Forrest; Zúñiga, Tiffany M.; Simpson, Richard J.; Katsanis, Emmanuel (Frontiers in Immunology, 2021)
The growth factor Flt3 ligand (Flt3L) is central to dendritic cell (DC) homeostasis and development, controlling survival and expansion by binding to Flt3 receptor tyrosine kinase on the surface of DCs. In the context of hematopoietic cell transplantation, Flt3L has been found to suppress graft-versus-host disease (GvHD), specifically via host DCs. We previously reported that the pre-transplant conditioning regimen consisting of bendamustine (BEN) and total body irradiation (TBI) results in significantly reduced GvHD compared to cyclophosphamide (CY)+TBI. Pre-transplant BEN+TBI conditioning was also associated with greater Flt3 expression among host DCs and an accumulation of pre-cDC1s. Here, we demonstrate that exposure to BEN increases Flt3 expression on both murine bone marrow-derived DCs (BMDCs) and human monocyte-derived DCs (moDCs). BEN favors development of murine plasmacytoid DCs, pre-cDC1s, and cDC2s. While humans do not have an identifiable equivalent to murine pre-cDC1s, exposure to BEN resulted in decreased plasmacytoid DCs and increased cDC2s. BEN exposure and heightened Flt3 signaling are associated with a distinct regulatory phenotype, with increased PD-L1 expression and decreased ICOS-L expression. BMDCs exposed to BEN exhibit diminished pro-inflammatory cytokine response to LPS and induce robust proliferation of alloreactive T-cells. These proliferative alloreactive T-cells expressed greater levels of PD-1 and underwent increased programmed cell death as the concentration of BEN exposure increased. Alloreactive CD4+ T-cell death may be attributable to pre-cDC1s and provides a potential mechanism by which BEN+TBI conditioning limits GvHD and yields T-cells tolerant to host antigen.